Synchronic peritoneal primary carcinoma with smooth muscle tumor of uncertain malignant potential (stump): case report - Solano, Alex (2022)
Primary peritoneal serous carcinoma (PSC) is a rare, aggressive, malignant neoplasm that is usually diagnosed incidentally, after having excluded an ovarian primary. Another rare entity is uterine smooth muscle tumor of uncertain malignant potential (STUMP), which is a borderline pathology between leiomyomas and leiomyosarcomas. Its synchronism has not been reported in the literature. We present the case of a 50-year-old woman with a twelve-month illness characterized by progressive abdominal distention, pain, weight loss, and edema in the lower limbs. The patient underwent surgery for a uterine tumor, to rule out sarcoma, finding, in addition to the gynecological neoplasia, solid peritoneal lesions. The histological diagnosis was STUMP synchronous with CSP. The evolution was unfavorable, dying three weeks after surgery. In the literature we don’t find cases of coexistence of these pathologies, so our finding represents a contribution in gynecological oncology.